STUDI POTENSI KOMPETISI ANTARA PASAR TRADISIONAL DENGAN TOKO MODERN PASCA PERATURAN PRESIDEN (PERPRES) NOMOR 112 TAHUN 2007 DI MADURA - Uswatun Hasanah; Indien Winarwati (Faculty of Law, Universitas Jenderal Soedirman, 2012)
The presence of Regulation the President No. 112 of 2007 is expected to realize the presence of a modern store that can compete in a healthy and fair with traditional markets. Although it has been mentioned that the establishment of modern stores have to pay attention spatial plan district, does not detract from the fact zoning violations on the establishment of a modern store. The study was based on indepth interviews with informants, traditional markets, modern store merchants, officials in the region Bangkalan, Sampang, Pamekasan, Sumenep.The results of this study can be concluded that the competition between the traditional market with modern stores after the enactment of Regulation the Presidential No.112 of 2007 increasingly stringent, as evidenced by the increasing proliferation of modern stores, especially the mini-sale systems and types of merchandise similar to the traditional markets. The factors that became the driving and inhibiting competition is no regulation and management matters. Efforts are being made in overcoming the constraints of competition through improved physical infrastructure, but have not touched on the professionalism of the management of traditional markets. Key words : competition, traditional market, modern store after the enactment Regulation the President No. 112 of 2007